Malignant mesothelioma tumours: molecular pathogenesis, diagnosis, and therapies accompanying clinical studies - Sahu, Ram Kumar; Ruhi, Sakina; Jeppu, Ashok Kumar; Al-Goshae, Husni Ahmed; Syed, Ayesha; Nagdev, Sanjay; Widyowati, Retno; Ekasari, Wiwied; Khan, Jiyauddin; Bhattacharjee, Bedanta; Goyal, Manoj; Bhattacharya, Sankha; et al. (Frontiers in Oncology, 2023)
The pathetic malignant mesothelioma (MM) is a extremely uncommon and confrontational tumor that evolves in the mesothelium layer of the pleural cavities (inner lining- visceral pleura and outer lining- parietal pleura), peritoneum, pericardium, and tunica vaginalis and is highly resistant to standard treatments. In mesothelioma, the predominant pattern of lesions is a loss of genes that limit tumour growth. Despite the worldwide ban on the manufacture and supply of asbestos, the prevalence of mesothelioma continues to increase. Mesothelioma presents and behaves in a variety of ways, making diagnosis challenging. Most treatments available today for MM are ineffective, and the median life expectancy is between 10 and 12 months. However, in recent years, considerable progress has already been made in understanding the genetics and molecular pathophysiology of mesothelioma by addressing hippo signaling pathway. The development and progression of MM are related to many important genetic alterations. This is related to NF2 and/or LATS2 mutations that activate the transcriptional coactivator YAP. The X-rays, CT scans, MRIs, and PET scans are used to diagnose the MM. The MM are treated with surgery, chemotherapy, first-line combination chemotherapy, second-line treatment, radiation therapy, adoptive T-cell treatment, targeted therapy, and cancer vaccines. Recent clinical trials investigating the function of surgery have led to the development of innovative approaches to the treatment of associated pleural effusions as well as the introduction of targeted medications. An interdisciplinary collaborative approach is needed for the effective care of persons who have mesothelioma because of the rising intricacy of mesothelioma treatment. This article highlights the key findings in the molecular pathogenesis of mesothelioma, diagnosis with special emphasis on the management of mesothelioma.